Perceived Language and Professional Competence of Senior High School English Teachers - PASCUAL, CATHERINE JOY (International Journal of Arts, Sciences and Education, 2022)
Language and professional competence of teachers is important for the success of instruction as it ensures a good model of the target language. Particularly their competence in applying new strategies, methods, and innovations, curriculum planning, assessment and reporting. Hence, this study explored teacher’s language and professional competence as perceived by them and their students. More specifically, a quantitative research design was used to assess English teachers' perceived language and professional competence in relation to their RPMS rating. Students rated teachers as "Very Satisfactory" in every area of language and professional competence. From the results, it is shown that respondents' profiles had no relation to their different language competence as assessed by their senior high school English teachers. In addition, the RPMS and teacher language and professional competence was also found to have no correlation. Thus, regardless of the RPMS evaluation quality, teachers' English language competence is affected or unaffected